Handbook for OSCE /OSPE Assessment in Obstetrics and Gynecology - Acharya, Neema (Handbook for OSCE /OSPE Assessment in Obstetrics and Gynecology, 2021)
An OSCE /OSPE is a type of Objective type of Test used in medical and paramedical sciences. It is structured to test knowledge, clinical or procedural skill and competence in a range of the same skills. It is a practical approach to learning and assessment. Recently the undergraduate and postgraduate curriculum for medical science in India has been reformed into competency based curriculum .Both OSCE and OSCPE are maor portion of the assessment method in this curriculum. This book is first of its kind in our country which we penned with the objective of providing a guide for undergraduate and postgraduate students of obstetrics and gynecologygive The chapters decription of common questions and answers asked at the stations and steps of procedure expected to be demonstrated at OSCE/ OSCPE stations in detail .It also provides a overview of common questions asked at grand viva (table viva voce).